مقاصد الشريعة وإشكالية دوران الأحكام بين التعبد والتعليل: درسة تأصيلية The objectives of sharia (maqasid) and the problem of the rulings between worship and reasoning: an applied fundamental study - Salhab, Belal B.S. (MIH Training and Consultancy Services and Al Hikmah Research and Publication Centre, 2023)
This paper aims to highlight the connection between the objectives of Sharia law and legal rulings of both reasoning and devotional aspects, it clarifies the extent of the connection between them, and fills the gap opened by lack of adequate study that could explains the extent of the connection between the objectives of Sharia law, which stands on the idea of justifying rulings and understanding the wisdom behind them, and the devotional rulings which are based on total submission to the commands of Almighty Allah without looking at its reasons and the rulings it contains; we need to balance between the worship aspect of some rulings, and what has been the concession of the majority of scholars saying that Allah has not legislated a ruling except for a purpose and objective, otherwise His legislation for it would be in vain? To answer this problem, the researcher followed a descriptive approach through which the basic features of the research terms is explained, and a synthetic analytical approach that discusses the scholars’ views, explores them deeply, and draws a complete picture that clarifies the extent of the relationship between the objectives of Sharia law and the justified and the rulings on worship. The research concludes that: The ruling on worship is the ruling which its partial standard cause cannot be tampered, even if it is possible to understand the wisdom behind its legislation. Reasoning is the basis of the idea of maqasid, and that there could not be objectives for rulings unless those rulings are reasoned. Finally, not understanding the partial reason for any ruling does not necessitate not understanding the general wisdom of that ruling, and therefore there is no conflict between the rulings on worship from which the wisdom could be understood, according to the majority opinion, and knowing their objectives. maqasid.